IPM PENGEMBANGAN MODEL LAB TERPADU BERBASIS KELAS SEBAGAI ALTERNATIF PENGELOLAAN YANG BAIK DALAM PEMBELAJARAN IPA SD KELAS TINGGI BAGI GURU-GURU SD SE KECAMATAN JEBRES SURAKARTA - Djaelani Djaelani; Peduk Rintayati; Siti Kamsiyati (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
The purpose science and technology for the Community Service is to provide counseling to teachers to do: (1) development of a laboratory model of the classroom as an integrated and where students of class IV and V in learning science. The design of this model is that in one corner of the room has been laid out practical tools ready to use with the IPA SD labeled with hints of good practice for use in experiments each item IPA SD, (2) refresh the entire scope of the basic concepts of materials science SD High Class with conduct demonstration experiments and preparation of simple science tools in the subject-subject taught in high grade,(3) creat simple IPA instrument lab from scrap materials or practical tools in the box KIT IPA SD.This activity contributes to equip and enrich the primary school teachers in managing good learning process focused on the study of elementary science with lab-based integrated development class area that facilitate experimental equipment ready for use (ready to use). Lab-based integrated area this class helps teachers in implementing the learning science in terms of the implementation of good practices in the IPA SD.Keywords : laboratory model of the classroom, managing good learning process